PERGI HAJI DENGAN UANG PINJAMAN DALAM PERSPEKTIF HUKUM ISLAM - Muchlis Bahar (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The purpose of this study is to analyze the perspective of Islamic law on going on a pilgrimage with debt. This research uses qualitative research with descriptive analysis approach. The type of data used in this research is secondary data. Going for Hajj is obligatory for every Muslim who has financial and health capabilities. The problem in this research is is it permissible to go for Hajj by way of debt. The findings of this study are that going for Hajj by borrowing money for the cost of the pilgrimage from another party, whether the other party is a rich person or a bank financial institution, is permissible (Mbah) as long as there is confidence that he is able to repay his debt. People who go to Hajj by borrowing money, including people who have the ability with the help of others can be called the existence of "al-Istitho'ah bi Ghairi". Then going for Hajj using borrowed money is the same as using money given by others, his Hajj is valid, accepted by Allah, he gets the reward and the obligation of Hajj has fallen from him.